Impact of Self-esteem on Smartphone Dependency among Young Adults: Mediated by Nomophobia - Aziz, Zoonish; Abbasi, Palwasha Nasir; Fazal, Saher (Annals of Human and Social Sciences, 2025)
The current research explored the effect of self-esteem on smartphone addiction in young adults, with nomophobia tested as a mediator. A total of 300 university students took part in the research using standardized tests: the Rosenberg Self-Esteem Scale, the Nomophobia Questionnaire, and the Smartphone Addiction Scale. Correlational and regression analyses identified a significant negative correlation between self-esteem and smartphone addiction. Mediation analysis also revealed that nomophobia partly mediated this association, indicating that lower self-esteem individuals tend to have higher levels of nomophobia, which further lead to higher levels of smartphone dependence. The results emphasize the need to tackle both self-view and anxiety in digital environments while promoting health technologies. It is advised that targeted interventions focusing on boosting self-esteem and alleviating nomophobia be integrated into digital literacy and mental health initiatives for young adults. Such programs can equip individuals with healthier coping strategies and foster more balanced, mindful engagement with technology.